3D porous chitosan-chondroitin sulfate scaffolds promote epithelial to mesenchymal transition in prostate cancer cells. (September 2020) - Xu, Kailei; Wang, Zi; Copland, John A.; Chakrabarti, Ratna; Florczyk, Stephen J.
Abstract: Prostate cancer (PCa) is a common cancer in men that is curable prior to metastasis, when its prognosis worsens. Chondroitin sulfate (CS) is found in the extracellular matrix of normal prostate tissue and PCa, with greater content in metastatic PCa. Biomaterial scaffolds containing CS have yet to be evaluated for tumor microenvironment applications. Three-dimensional porous chitosan-CS (C-CS) scaffolds were developed and evaluated for PCa culture. Three C-CS scaffold compositions were prepared with 4 w/v% chitosan and 0.1, 0.5, and 1.0 w/v% CS and named 4-0.1, 4-0.5, and 4-1, respectively. The C-CS scaffolds had 90–95% porosity, average pore sizes between 143 and 166 μm, and no significant difference in scaffold stiffness. PC-3 and 22Rv1 PCa cells were cultured on the C-CS scaffolds to study the effect of CS on PCa growth and epithelial to mesenchymal transition (EMT). All C-CS scaffold compositions supported PCa growth and the 4-1 scaffolds had the greatest cell numbers for both PC-3 and 22Rv1. The C-CS scaffolds promoted upregulated EMT marker expression compared to 2D cultures with the greatest EMT marker expression in 4-1 scaffolds. Increasing CS concentration promoted upregulated vimentin expression in PC-3 cultures and N-cadherin and MMP-2 expression in 22Rv1 cultures. C-CS scaffolds promoted docetaxel drug resistance in PC-3 and 22Rv1 cultures and the 4-1 scaffold cultures had the greatest drug resistance. These results indicate that C-CS scaffolds are a promising in vitro platform for PCa. Graphical abstract: Image 1